The Influence of Accounting Information Systems, E-Commerce, Financial Literacy, Financial Technology, and Product Innovation on the Performance of MSMEs in Jepara Regency - Miqbas, Fahdil Amjad; Zuliyati, Zuliyati; Handayani, Retno Tri (IAIN Kudus, 2024)
MSMEs are a big contributor to the country's economy. This is evidenced by the ability of MSMEs to survive amid an economic crisis, even though many large companies have gone bankrupt or even stopped operating. This study empirically examines how accounting information systems, e-commerce, financial literacy, financial technology, and product innovation affect the performance of MSMEs. This study has a population of all MSMEs registered at Diskopukmnakertrans Jepara Regency. The sampling technique was a purposive sampling of 400 respondents. Multiple linear regression analysis techniques using SPSS version 26 are the analytical techniques used in this study. This study shows that the variables of accounting information systems, e-commerce, financial literacy, financial technology, and product innovation have a positive and significant influence on the performance variables of MSMEs, both simultaneously and partially.